Oxidative stress, inflammation and treatment response in major depression. (February 2017) - Lindqvist, Daniel; Dhabhar, Firdaus S.; James, S. Jill; Hough, Christina M.; Jain, Felipe A.; Bersani, F. Saverio; Reus, Victor I.; Verhoeven, Josine E.; Epel, Elissa S.; Mahan, Laura; Rosser, Rebecca; Wolkowitz, Owen M.; et al.
Highlights: Markers of inflammation and oxidative stress were higher in MDD. SSRI treatment response was associated with oxidative stress and inflammation. Medications, somatic conditions or health behaviors did not affect the findings. Abstract: Objective: Increased inflammation and oxidative stress have been shown in Major Depressive Disorder (MDD), although there is significant heterogeneity across studies. Whether markers of inflammation and oxidative stress are associated with antidepressant treatment response in MDD is currently unclear. The goals of the present study are to investigate markers of inflammation and oxidative stress in unmedicated MDD subjects and controls and test the relationship between these markers and antidepressant response in MDD subjects. Methods: Interleukin (IL)-6, tumor necrosis factor (TNF)-α, C-reactive protein, F2-isoprostanes, 8-OH 2-deoxyguanosine (8-OHdG), glutathione peroxidase, glutathione, and vitamin C were quantified in blood samples from 50 unmedicated MDD subjects and 55 healthy controls. Depression symptom severity was rated with the 17-item Hamilton Depression Rating Scale (HDRS). All subjects were somatically healthy and free from medications that could interfere with inflammation and oxidative stress markers. A subgroup of 22 MDD subjects underwent open-label selective serotonin reuptake inhibitor (SSRI) antidepressant treatment for eight weeks, after which blood sampling and the HDRS were repeated. Antidepressant treatment "response" was defined as ≥50% decrease in HDRS ratings over 8 weeks of treatment. Results: After controlling for the effects of age, sex, body mass index and smoking, MDD subjects had significantly higher levels of IL-6 (p < 0.001), TNF-α (p < 0.001), 8-OHdG (p = 0.018), and F2-isoprostanes (p = 0.012). Compared to Responders, Non-responders to SSRI antidepressant treatment had higher levels of F2-isoprostanes at baseline (p = 0.006), and after eight weeks of treatment (p = 0.031). Non-responders showed a significant increase in 8-OHdG over the course of treatment (p = 0.021), whereas Responders showed a significant decrease in IL-6 over the course of treatment (p = 0.019). Conclusion: Our results are in line with previous reports of increased levels of markers of inflammation and oxidative stress in MDD. Moreover, poorer antidepressant treatment response was related to higher baseline levels of the major oxidative stress marker, F2-isoprostanes, in vivo . Further, antidepressant response was associated with changes in oxidative (8-OHdG) and inflammatory (IL-6) markers.